Accuracy of elastography point quantification and steatosis influence on assessing liver fibrosis in patients with chronic hepatitis C. (1st August 2016) - Conti, Fabio; Serra, Carla; Vukotic, Ranka; Fiorini, Erica; Felicani, Cristina; Mazzotta, Elena; D'Errico, Antonietta; Verucchi, Gabriella; Lenzi, Marco; Andreone, Pietro
Abstract: Background & Aims: Elastography point quantification is a novel non‐invasive method for the assessment of liver fibrosis by measuring liver stiffness. The aim of this study was to evaluate the accuracy of elastography point quantification for the diagnosis of liver fibrosis and to assess impact of steatosis on liver stiffness measurement, in a cohort of patients with chronic hepatitis C. Methods: In this single‐centre cross‐sectional study, 211 consecutive patients with chronic hepatitis C, scheduled for liver biopsy, were examined with the elastography point quantification technology. On the same day, all patients underwent clinical examination, laboratory tests and abdominal ultrasound. Results: The best cut‐offs of liver stiffness measurement were 6.16 kPa for the diagnosis of significant fibrosis (≥S3) and 6.79 kPa for advanced fibrosis (≥S4). Areas under the receiver operating characteristic curve were 0.831 (CI: 0.773–0.880) for significant fibrosis, and 0.954 (CI: 0.916–0.978) for advanced fibrosis. Among patients within the same fibrosis stages (S0–S2 and S3–S6; S0–S3 and S4–S6), mean liver stiffness measurement values were similar in patients with steatosis (≥10% at liver biopsy or detected by ultrasound) compared to those without. Discordance between elastography point quantification and histology were affected by the presence of BMI>30 kg/m 2 ( P =.047, CI: 0.136–0.988 and P =.020, CI: 0.083–0.812 respectively). Conclusions: In patients with chronic hepatitis C, elastography point quantification is an accurate non‐invasive method for the diagnosis of significant and advanced fibrosis. The presence of obesity is a risk factor for misclassification of significant and advanced liver fibrosis.